Research Progress on Applications of Metasurface-Based Optical Image Edge Detection Technology - Yuying Jiang; Qingcheng Sun; Tauseef Abbas; Hongyi Ge; Guangming Li; Keke Jia; Yuwei Bu; Huifang Zheng (Photonics)
With the rapid development of metasurface technology, metasurfaces have gained significant attention in optical edge detection. Owing to their precise control over the phase, amplitude, and polarization state of electromagnetic waves, metasurfaces offer a novel approach to edge detection that not only overcomes the size limitations of traditional optical devices but also significantly enhances the flexibility and efficiency of image processing. This paper reviews recent research advances in metasurfaces for optical edge detection. Firstly, the principles of phase-controlled metasurfaces in edge detection are discussed, along with an analysis of their features in different applications. Then, methods for edge detection based on polarization and dispersion modulation of metasurfaces are elaborated, highlighting the potential of these technologies for efficient image processing. In addition, the progress in multifunctional metasurfaces is presented, offering new perspectives and application prospects for future optical edge detection, along with a discussion on the limitations of metasurface-based edge detection technologies and an outlook on their future development.